Tax Avoidance, Board of Commissioners, And Leverage's Influence on Firm Value With Profitability As Moderation - Andre Andre; Herman Ruslim (Return : Study of Management, Economic and Bussines, 2023)
One way to attract investors is to see how a company's performance can be rated well. The purpose of this study is to obtain empirical evidence on the effect of tax avoidance, board of commissioners, and leverage on firm value with profitability being the role of moderating the relationship between the independent variable and the dependent variable. The data used in this study used quantitative data from financial statement data registered on the IDX in 2018 – 2021 with 124 samples used using the purposive sampling method. The hypothesis was tested by regression analysis of panel data. The tests conducted found that tax avoidance and the board of commissioners had a significant effect on firm value, leverage did not affect firm value. The results of the interaction test show that profitability cannot moderate between tax avoidance variables and leverage on firm value, but profitability can moderate the board of commissioners on firm value with result of Adjusted R2 value gets a result of 22.63% , where there are still 77.37% more variables that can affect the dependent variable, including: Firm Value.